Deep Space Thinking: What Elon Musk’s Idea to Nuke Mars Teaches Us About Regulating the “Visionaries and Daredevils” of Outer Space - Herron, Thomas J. (Columbia Journal of Environmental Law, 2019)
Elon Musk, founder of California-based aerospace company SpaceX, was recently called a “supervillain” on The Late Show with Stephen Colbert after revealing his idea to detonate thermonuclear devices over the poles of Mars. Musk does not have sinister intentions; he wants to terraform the Martian atmosphere so that future generations of humans can live there.3 Musk has long been an advocate of colonizing Mars, arguing that a multi-planetary presence can safeguard the survival of humanity in the future, especially if a catastrophic event ever occurs on Earth. Musk believes that Mars has great potential to support human life in the future, and his plan to create a habitable Martian atmosphere is intriguing. Special nuclear devices would be detonated in space over the planet’s polar ice caps, “creating two tiny pulsing ‘[S]uns’ over the regions.” In theory, generating large amounts of heat over the Martian poles could vaporize and release carbon dioxide contained in Mars’ polar ice caps, thickening the atmosphere. A thicker atmosphere could trap heat from the Sun, which normally is absorbed by the planet and then released as infrared radiation. Retaining more heat from the Sun could trigger a cascading greenhouse effect by releasing more carbon dioxide and continuing to heat up Mars until the surface pressure increased enough for liquid water to exist.10 Formation of liquid water could be very favorable for oxygen-producing plants, and thus, human survival. Musk’s proposal raises fascinating legal questions about non-government activity in outer space. This Note will explore the legal implications of his idea to terraform Mars using fusion nuclear technology. It is not an endorsement of using nuclear devices to alter the Martian atmosphere. Far too many ethical, environmental, technological, and political questions must be addressed before the issue can be decided. Rather, this Note is intended to show that international and national space laws dance around the questions surrounding Musk’s proposal without providing a clear-cut legal answer. But incorporating his idea, however farfetched, into any discussion about the future legal rights of non-government entities in outer space will steer lawmakers toward preferred, consensus outcomes as the law evolves. Musk’s unusual idea is relevant to that discussion because it will help lawmakers demarcate the appropriate legal boundaries of non-government activity in outer space. Part II prefaces the legal analysis by providing basic information about the Martian atmosphere and the initial public reaction to the use of nuclear devices there. Part III analyzes the legality of Musk’s idea under international law. Part IV analyzes the legal implications of Musk’s terraforming idea under U.S. law; under existing international law, the U.S. government must regulate private space entities like Musk who are within its jurisdiction. Part V argues that it is unwise for international and U.S. lawmakers to characterize farsighted ideas like Musk’s as excessively optimistic,13 or dismiss them because they lack clear legal answers. Regardless of whether Musk’s plan to use nuclear devices over Mars is a bad idea, ignoring its legal implications altogether is bad policy.